2011
DOI: 10.2223/jped.2119
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis A in children and adolescents

Abstract: Objectives: To determine the seroprevalence of hepatitis A (HAV) in children and adolescents aged 1 to 14 years, and to identify factors associated with a history of infection.Methods: This was a cross-sectional epidemiological study, conducted form February to August 2006 in the city of Curitiba, Paraná, Brazil, and the surrounding municipalities (Greater Curitiba). Laboratory analysis comprised qualitative assay for total HAV antibodies in whole blood samples.Results: A total of 901 children and adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
3
4
1
3
Order By: Relevance
“…As observed by other authors (8,10,14) , living environment clusters were predictive of positivity for anti-HAV. In the settlement projects investigated, individuals who reported more than five people living in the same household had almost a 20% risk of being anti-HAV positive (RP:1.18; P=0.007).…”
Section: Discussionsupporting
confidence: 80%
“…As observed by other authors (8,10,14) , living environment clusters were predictive of positivity for anti-HAV. In the settlement projects investigated, individuals who reported more than five people living in the same household had almost a 20% risk of being anti-HAV positive (RP:1.18; P=0.007).…”
Section: Discussionsupporting
confidence: 80%
“…In the Brazilian Northeast, one of the country's poorest regions, the highest prevalence is found in children under 5 years 6,7 . Other studies conducted in poor areas from wealthier municipalities around the country, such as the city of Santos, São Paulo in 2007 8 and the metropolitan region of Curitiba, Paraná in 2006 9 found similar results to those obtained in the Northeast, with a higher frequency of HAV infection observed in children under 5 years.…”
Section: Discussionsupporting
confidence: 68%
“…In Brazil, seroprevalence studies conducted recently mainly in urban areas, showed a consistent decrease of the incidence rates in childhood 4,5,6,7,8,9,10 . Decrease in HAV circulation 8,9,11,12 as well as a progressive decline in fatal cases related to HAV infection in all Brazilian regions 8 have also begun to be noticed.…”
mentioning
confidence: 84%